Nutritional habits, inhibitory control, and emotional reactivity to healthy and unhealthy food cues in non-obese female students: insights from heart rate variability - Sarlo, Michela; Del Popolo Cristaldi, Fiorella; Buodo, Giulia; Belacchi, Carmen (Frontiers in Nutrition, 2025)
BackgroundResearch shows that the nutritional habits of university students do not follow the national recommendations. While most studies have focused on the increased risk of overweight/obesity, avoiding unhealthy food or maintaining a normal weight does not necessarily result in a regular consumption of healthy essential nutrients.MethodsThe present study was aimed at investigating the interplay between emotional reactivity and inhibitory control in 42 non-obese female students exposed to healthy (fish/lean meat, fruit/vegetables) and unhealthy (savory and sweet junk food) food pictures, after an average fasting of 7.5 h. Resting heart rate variability (HRV) was assessed as a physiological index of self-regulation, exploring its association with emotional reactivity and inhibitory control, as well as its predictive role in nutritional habits. We measured valence, arousal and craving during a free viewing time task and assessed inhibitory and attentional control through an emotional Go/NoGo task. Hunger, nutritional habits and frequency of physical activity were also collected.ResultsUnhealthy foods elicited higher pleasantness, arousal and craving than healthy foods, indicating stronger appetitive motivation. Emotional reactivity was predicted by hunger or fasting duration as a function of food type. Higher HRV predicted slower reaction times to Go stimuli for all food types except fruit/vegetables. HRV and physical activity negatively predicted the habitual consumption of sweet junk food and positively predicted that of fruit/vegetables.ConclusionOur results provide novel insights into the mechanisms underlying dietary self-regulation in non-obese female students, highlighting the significant role of resting HRV and physical activity in promoting healthy dietary choices and limiting junk food intake.